USING THEME-BASED APPROACH TO IMPROVE STUDENTS’ NARRATIVE WRITING ACHIEVEMENT - Febrianita Prasasti; Muslih Hambali; Fiftinova Fiftinova (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: The objectives of this study were to find out whether or not there were 1) a significant difference in students’ narrative writing achievement before and after they were taught by using Theme-Based Approach, and 2) a significant improvement in students’ narrative writing achievement in terms of content (purpose and narrative development). This study was a pre-experimental study which applied pretest-posttest one group design. The population was the 10th grade students of SMA N 1 Indralaya Utara in academic year 2013/2014 with a total number of 123 students. The total number of the sample was 32 students that was taken purposively. The data were obtained by means of writing test. First, the result showed that the students got better scores in the posttest than in the pretest. The calculation of paired-sample t-test showed that there was a significant difference in students’ narrative writing achievement before and after the treatment. This showed by the t-obtained (12.042) that was higher than the t-table (2.041). Second, the calculation of paired-sample t-test per aspect of writing showed that content (purpose and narrative development) was the most significantly improved aspect out of the five aspects. In other words, there was a significant improvement in students narrative writing in terms of content (purpose and narrative development) after they were taught by using Theme-Based Approach. Key words:narrative text, writing achievement, theme-based approach, improve